Les rencontres virtuelles – une nouvelle opportunité de redéploiement international pour l’enseignement du français de la diplomatie ? - Wojakowska , Marta (Neofilolog, 2023)
The aim of this article is to investigate student perception of distance learning in “French for diplomats” , as well as to observe whether and to what extent recent developments in virtual learning environments in language learning have proven effective and may have promoted international collaboration. The study, carried out in 2021/2022 at the Institute of Romance Studies of the University of Warsaw, revealed that a significant proportion of students with experience of the “French for diplomats” distance course are very satisfied with the virtual courses. After observing the encouraging reactions of learners during the course, we decided to carry out our research on their experiences. We started from the premise that distance learning ofthe language for specific purposes could be beneficial to the learning process. Our reflections focused mainly on building intercultural competence, but also on the changing representations of the profession of diplomat and, consequently, on the opportunities that virtual courses open. It was found that the shift from face-to-face to digital has given teachers new tools and modalities that enrich the quality of the lesson. The teaching of specialized languages such as “French for diplomats” can nowadays include videoconferencing with a diplomat based in Guatemala or Brussels. Thus, the abandonment of face-to-face lessons has given back pedagogical freedom and helped teachers look for original solutions.